Generalized relaxed elastic line on an oriented surface - Özkan, G.; Yücesan, A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the relaxed elastic line in a more general case on an oriented surface. In particular, we obtain a differential equation with three boundary conditions for the generalized relaxed elastic line. Then we analyze the results in a plane, on a sphere, on a cylinder, and on the geodesics of these surfaces.